Pola Umum Perilaku Religius Sebagai Orde Moral Dalam Kerangka Teologis Suku Primitif di Indonesia - Imam Madi (Institut Seni Indonesia Surakarta, 2004)
The visualistict phenomena in the archaeology artefact of primitive ethnic in Indonesia and even in the world shows streotifacy, it means that the culture thing or the culture product which is produced, shows the equal characteristic as if the long culture contact is never happened and being continues; that in the reality, it never done. Attention to the artefact of the primitive ethnic on the Leang-Leang Cave and compare with the other artefact have found which has some far space of geographic. There are going to shows the same touched pattern. The point questions are What, Why, and How is it able to be happened ? By this editorial, we try to analyse the behaviour aspect of party who doing the culture, it is about the common indication which isshown in the psychology aspect to respond the stimulus outside themselves. Certainly the things found is the assumption which is shaped according to the theory of several knowledge that is connect by studying of books, as far as this situation does not have a field study. This paper is just looking for the point of thinking pattern indications commonly of party who doing the culture in that time, where it is able to get the conclusion become the morality leadership of primitive ethnic in order to catch the live mystery that have been keep them to the freedom or self independence (outlet).Keyword : psychology, culture.